2004
DOI: 10.1210/jc.2004-0122
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Insulin Secretion in the Turner Metabolic Syndrome

Abstract: An increased prevalence of impaired glucose homeostasis (IGH) and diabetes mellitus is reported in monosomy X, or Turner syndrome (TS). To determine whether IGH is an intrinsic feature of this syndrome, independent of obesity or hypogonadism, we compared results of a standard oral glucose challenge in age- and body mass index-matched women with TS and with karyotypically normal premature ovarian failure (POF). Fasting glucose levels were normal in both groups, but glucose values after oral glucose challenge we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
91
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(106 citation statements)
references
References 26 publications
9
91
0
6
Order By: Relevance
“…injection of glucose at 0.3 or 0.5 g/kg showed C-peptide and insulin levels intermediate between those of pigs and monkeys. The fold increases between time 0 and 5 min and between time 0 and 15 min were (range) 2.5-3.5 and 2.1-3.0 respectively for C-peptide and 6.3-11.4 and 4.0-5.0 for insulin [24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 93%
“…injection of glucose at 0.3 or 0.5 g/kg showed C-peptide and insulin levels intermediate between those of pigs and monkeys. The fold increases between time 0 and 5 min and between time 0 and 15 min were (range) 2.5-3.5 and 2.1-3.0 respectively for C-peptide and 6.3-11.4 and 4.0-5.0 for insulin [24][25][26][27][28][29][30].…”
Section: Resultsmentioning
confidence: 93%
“…However, the hypothesis of gene haploinsufficiency for overweight was not upheld by Ohman et al because of a candidate locus for obesity located on X short arm Xp24 (21). Nevertheless, Bakalov et al demonstrated an insulin secretion defect in TS patients compared with both 46,XX patients with diminished ovarian reserve and controls matched according to age (22); they illustrated that haploinsufficiency of genes located on X chromosome accounted for pancreatic b-cell impairment. This finding could partly explain the positive correlation demonstrated in our study, with proportional pancreatic cell impairment depending on the percentage of aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism is altered in TS and type 2 diabetes is seen frequently (9); insulin resistance has been reported in some studies on children (10,11), while studies on adults have pointed towards b-cell failure rather than insulin resistance as the primary defect in glucose homeostasis (5,12,13). The pathogenesis behind progressive b-cell failure is not clear, and further characterization is necessary.…”
Section: Introductionmentioning
confidence: 99%